Novelties and notes on Tradescantia (Commelinaceae) from Brazil - Hassemer, Gustavo; Funez, Luís A. (Phytotaxa, 2020)
We present here novelties and notes on Tradescantia from Brazil. More specifically, we describe a narrowly endemic new species from southern Brazil (T. insularis), create a new name at the species rank (T. catharinensis) for T. crassula var. gaudichaudii, discuss the taxonomy of T. schwirkowskiana and T. serrana, and lectotypify T. tenella and present the first record of this species in the Southeast Region of Brazil. Finally, we provide an identification key to Tradescantia in Brazil.